Mechanical properties of concrete with recycled plastic coarse aggregate partial replacement - Alkotami, Laura (Kansas State University, 2023)
Concrete is the second most used material in the building industry, after water (Global Cement and Concrete Association, 2020). Concrete is made up of cement, water, and natural aggregates such as fine and coarse aggregates. To prevent the earth from losing natural resources to make concrete, a replacement for these materials must be found. Many researchers have found that a possible replacement for coarse aggregate in concrete is recycled plastic waste. These studies have been conducted to test the mechanical properties: compressive strength, splitting tensile strength, modulus of rupture, and modulus of elasticity of concrete with partial plastic waste replacement as coarse aggregate. The studies differ from each other based on the type of plastic used, the water-to-cementitious ratios (w/c), the amount of plastic replacement, and the concrete mix. This thesis examines and compares the results of previous studies/tests conducted on concrete with the replacement of coarse aggregate with plastic to possibly find trends or recommendations for future use. Several tables and graphs that summarize the findings in these studies were made. For the compressive strength and the splitting tensile strength, results from 10%, 15%, and 20% replacements were tabulated and graphed. However, due to the lesser number of tests done on the modulus of rupture, only 10% and 20% replacement results were tabulated and graphed. The graphs were made based on the resulting strength after the partial replacement vs curing days. In contrast, the graph conducted on the modulus of elasticity was based on the resulting modulus of elasticity vs the percentage of plastic replacement. It was shown that up to a certain level, the properties of plastic waste could be suitable to produce new concrete. However, due to the varying results from the studies it was difficult to find trends as each study had a different concrete mix with not much information or discussion provided. Shown in most studies examined, as the amount of plastic waste replacement increases the lower the compressive strength, splitting tensile strength, and modulus of elasticity. However, the modulus of rupture resulted in a slight increase or no change in strength after the plastic replacement. Very little information was provided in the studies examined herein, which led to no common trends or conclusions being found. This thesis may be used as a good resource to find summarized tables and graphs on the previous studies examining the mechanical strength of concrete containing partial plastic waste replacement for coarse aggregate.
Keywords: Concrete; Coarse aggregate; Mechanical properties; Plastic replacement